2015
DOI: 10.1104/pp.15.00537
|View full text |Cite
|
Sign up to set email alerts
|

An Overdose of the Arabidopsis Coreceptor BRASSINOSTEROID INSENSITIVE1-ASSOCIATED RECEPTOR KINASE1 or Its Ectodomain Causes Autoimmunity in a SUPPRESSOR OF BIR1-1-Dependent Manner

Abstract: The membrane-bound BRASSINOSTEROID INSENSITIVE1-ASSOCIATED RECEPTOR KINASE1 (BAK1) is a common coreceptor in plants and regulates distinct cellular programs ranging from growth and development to defense against pathogens. BAK1 functions through binding to ligand-stimulated transmembrane receptors and activating their kinase domains via transphosphorylation. In the absence of microbes, BAK1 activity may be suppressed by different mechanisms, like interaction with the regulatory BIR (for BAK1-INTERACTING RECEPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 92 publications
2
37
0
1
Order By: Relevance
“…To further explore the role of target genes in plant immunity, we attempted to generate overexpression lines of resistant target gene versions and achieved an overexpressor of the AtWNK2r version ( AtWNK2 r-OE) (Fig.S5a) in the atwnk2-2 background. AtWNK2r -OE plants showed ectopic cell death in distance from infection sites (Fig.S14a), as previously described for overexpression lines of other immunity factors, such as At BAK1 (Domínguez-Ferreras et al, 2015). Moreover, infection structures frequently displayed aberrant swelling-like structures and extensive branching of hyphae instead of the regular pyriform haustoria formed in atwnk-2-2 (Fig.S14b), further supporting a role for AtWNK2 in immune reaction.…”
Section: Resultssupporting
confidence: 83%
“…To further explore the role of target genes in plant immunity, we attempted to generate overexpression lines of resistant target gene versions and achieved an overexpressor of the AtWNK2r version ( AtWNK2 r-OE) (Fig.S5a) in the atwnk2-2 background. AtWNK2r -OE plants showed ectopic cell death in distance from infection sites (Fig.S14a), as previously described for overexpression lines of other immunity factors, such as At BAK1 (Domínguez-Ferreras et al, 2015). Moreover, infection structures frequently displayed aberrant swelling-like structures and extensive branching of hyphae instead of the regular pyriform haustoria formed in atwnk-2-2 (Fig.S14b), further supporting a role for AtWNK2 in immune reaction.…”
Section: Resultssupporting
confidence: 83%
“…From a suppressor screen of bir1‐1 , we found that BAK1 is also required for activation of cell death and defense responses in the bir1‐1 mutant, suggesting that BAK1 also plays a positive role in promoting cell death and plant defense. This is consistent with the notion that over‐expression of BAK1 leads to spontaneous cell death (Belkhadir et al ., ; Dominguez‐Ferreras et al ., ). As BAK1 functions as a general co‐receptor for multiple RLKs involved in different biological processes, the opposite functions of BAK1 in plant immunity are most likely facilitated by the receptor‐like kinases (RLKs) it interacts with.…”
Section: Discussionmentioning
confidence: 97%
“…BIR1 is a negative regulator of several resistance pathways in which BAK1 and SOBIR1 have concerted roles (Gao et al ., ; Dominguez‐Ferreras et al ., ; Liu et al ., ). Here we provide compelling evidence that BIR1 transcription is positively regulated by SA and propose that TRV triggers NPR1‐dependent expression of BIR1 during the infection by increasing SA concentrations in the infected tissue.…”
Section: Discussionmentioning
confidence: 99%